Association between hypomagnesemia and mortality among dialysis patients: a systematic review and meta-analysis - Huang,Chi-Ya; Yang,Chi-Chen; Hung,Kuo-Chuan; Jiang,Ming-Yan; Huang,Yun-Ting; Hwang,Jyh-Chang; Hsieh,Chih-Chieh; Chuang,Min-Hsiang; Chen,Jui-Yi (PeerJ, 2022)
Background Malnutrition-inflammation-atherosclerosis (MIA) syndrome is caused by the inflammatory cytokines in end stage renal disease (ESRD) patients, and MIA complex-related factors may be associated with hypomagnesemia and mortality. However, the association between serum magnesium level and mortality for dialysis patients is still not clear. Additionally, no meta-analysis has investigated the impact of serum magnesium on peritoneal dialysis and hemodialysis, separately. Methods We searched published studies in PubMed, Embase, Cochrane, Collaboration Central Register of Controlled Clinical Trials, and Cochrane Systematic Reviews through April 2022. Studies associated with serum magnesium and all-cause mortality or cardiovascular (CV) mortality in ESRD on kidney replacement therapy (KRT) patients were included. A hazard ratio (HR) with 95% confidence intervals (CI) was used to report the outcomes. Results Twenty-one studies involving 55,232 patients were included. Overall, there was a significant association between hypomagnesemia and all-cause mortality for dialysis patients (HR: 1.67, 95% CI [1.412–2.00], p < 0.001; certainty of evidence: moderate) using a mixed unadjusted and adjusted HR for analysis. There was also a significantly increased risk of CV mortality for individuals with hypomagnesemia compared with the non-hypomagnesemia group (HR 1.56, 95% CI [1.08–2.25], p < 0.001; certainty of evidence: moderate). In addition, a subgroup analysis demonstrated that hypomagnesemia was associated with a high risk of both all-cause mortality and CV mortality (all-cause mortality, HR:1.80, 95% CI [1.48–2.19]; CV mortality, HR:1.84, 95% CI [1.10–3.07]) in hemodialysis (HD) patients, but not in participants receiving peritoneal dialysis (PD; all-cause mortality, HR:1.26, 95% CI [0.84–1.91]; CV mortality, HR:0.66, 95% CI [0.22–2.00]). The systematic review protocol was prespecified and registered in PROSPERO [CRD42021256187]. Conclusions Hypomagnesemia may be a significant risk factor for all-cause mortality and CV mortality in KRT patients, especially in those receiving hemodialysis. However, because of the limited certainty of evidence, more studies are required to investigate this association.
Keywords: Hypomagnesemia; Magnesium; Dialysis; Mortality; Hemodialysis